Kewenangan Daerah Dalam Melaksanakan Hubungan Luar Negeri (Studi Kasus di Propinsi Jawa Barat dan DIY ) - Jawahir Thontowi (Fakultas Hukum Universitas Islam Indonesia, 2009)
Local governments, though they may establish international collaboration, they can not be considered as a subject of law in the international law, but rather as an auxiliary instrument of the central government. From the perspective of international law, the responsibilities raised by such international collaboration or international agreement is not in the hand of local government. Another significant point with regards to the said collaboration is that this is also does not contradict with the principle of national unity (NKRI). Because, the local government is merely as an agent of the state which is a subject of international law. In case of any disputes that may the agreements cause shall also be emphasized to be settled within national legal system of Indonesia.Keywords: Authority, Local Government, Collaboration, MoU, Sister City, Foreign Private